Study the Effect of Lemongrass and Rosemary Extracts against Bacterial Pathogens (World Journal of Experimental Biosciences, 2024)
The study aims to study the antibacterial effects of lemongrass and rosemary extracts against different types of bacteria. According to studies, rosemary extract has antibacterial properties against both Gram-positive and Gram-negative bacteria, such as Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus. Bioactive substances including rosmarinic acid and carnosic acid are responsible for the antibacterial properties of rosemary extract. Salmonella enterica, Listeria monocytogenes, and Bacillus cereus are just a few of the microorganisms that lemongrass extract has been shown to have antibacterial activity against. Citral a significant part of the essential oil, is the main cause of lemongrass’s antibacterial qualities. It has also been discovered that combining the extracts of lemongrass and rosemary has a synergistic effect that increases the antibacterial action against specific bacteria. It is thought that the various modes of action of the bioactive substances included in these extracts are what cause this synergistic impact. All things considered, the data that is now available points to the possibility of using extracts of rosemary and lemongrass as natural antibacterial agents against a range of harmful microorganisms.